Dutch Respelling Rules for English and German Medical Word Lists - Offerhaus, G. J. A.; Tersmette, A. C.; Moore, G. W.; Hershey, Johanna; Polacsek, R. A. (Methods of Information in Medicine, 1987)
Computer translation programs for foreign language texts have recently become available commercially and in the public domain, but large medical lexicons for these programs are not readily available. It has been shown that many English words can be “respelled” to form their corresponding translations in other Western European languages. We have used lists of 139,451 English and 185,137 German medical terms to generate respeliings in the Dutch language. The English list yielded 39,035 Dutch respeliings, and the German list yielded 56,683 respeliings. Medical respelling rules can substantially lower the effort of installing and maintaining a medically oriented computer translation program.
Keywords: Respelling Rules; Word Segmentation; Computer Translation Program; Dutch Language; English Language; German Language